PENANAMAN POHON MANGROVE DI DESA MANGUNHARJO TUGU SEMARANG SEBAGAI BENTUK KEPEDULIAN LINGKUNGAN - Yuliani Rahmah (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2019)
(Title    : Mangrove Tree Planting As Environmental Awareness Activity). This activities goal is to open up insights on the importance of the natural preservation of the coastal environment, how to maintain the balance of the ecosystem in it and hone awareness of the coastal areas of Semarang environment. Through this community service activity (Pengabdian Kepada Masyarakat), the participants are encouraged to make improvements and maintain the environment around the coast. With the enviromental activist explanation and the practice of planting directly on the abrasion site, it is hoped that it can foster self-confidence, environment awareness, and stimulan the ability to work well together in supporting environmental care programs.